Impact of dipeptidyl peptidase-4 inhibitors on glucose-dependent insulinotropic polypeptide in type 2 diabetes mellitus: a systematic review and meta-analysis - Chai, Shangyu; Zhang, Ruya; Carr, Richard David; Deacon, Carolyn F.; Zheng, Yiman; Rajpathak, Swapnil; Chen, Jingya; Yu, Miao (Frontiers in Endocrinology, 2023)
Aims: Glucose-dependent insulinotropic polypeptide (GIP) confers a variety of metabolic benefits in type 2 diabetes mellitus (T2DM). This meta-analysis was conducted to investigate the impact of dipeptidyl peptidase 4 (DPP4) inhibitors on GIP levels in T2DM patients. Methods: Medline (PubMed), CENTER (Cochrane Library), and Embase (Ovid) were searched and randomized controlled trials (RCTs) evaluating the impact of DPP4 inhibitors on fasting and postprandial GIP levels were obtained. For postprandial GIP, only studies with the data of GIP changes reported as the total area under the curve (AUCGIP) using a meal or oral glucose tolerance test was included. A random-effects model was used for data pooling after incorporating heterogeneity. Results: Overall, 14 RCTs with 541 T2DM patients were included. Compared to placebo/no treatment, the use of DPP4 inhibitors significantly increased the fasting GIP level (standard mean difference [SMD]: 0.77, 95% confidence interval [CI]: 0.48–1.05, P<0.001; I2=52%) and postprandial AUCGIP (SMD: 1.33, 95% CI: 1.02–1.64, P<0.001; I2=65%). Influence analysis by excluding one dataset at a time showed consistent results. Sensitivity analyses only including studies with radioimmunoassay showed also consistent results (fasting GIP: SMD: 0.75, 95% CI: 0.51–1.00, P<0.001; I2=0%; and postprandial AUCGIP: SMD: 1.48, 95% CI: 1.18–1.78, P<0.001; I2=54%). Further subgroup analyses demonstrated that the influence of DPP4 inhibitors on fasting and postprandial GIP levels in T2DM patients was not significantly changed by study characteristics such as study design, patient mean age, baseline glycated hemoglobin (HbA1c) concentration, body mass index (BMI), background treatment, treatment duration, or method for postprandial GIP measurement (all P for subgroup effects <0.05). Conclusions: The use of DPP4 inhibitors effectively increases the fasting and postprandial GIP concentrations in T2DM patients.